Scapholunate Ligament Injury and the Effect of Scaphoid Lengthening - Furey, Matthew J.; White, Neil J.; Dhaliwal, Gurpreet S. (Journal of Wrist Surgery, 2020)
Objective We hypothesized that lengthening the scaphoid in a model of scapholunate ligament injury (SLI) will result in correction of radiographic markers of dorsal intercalated segment instability (DISI) deformity.Materials and Methods An SLI with DISI deformity was created by sectioning the SL ligament, the palmar radiocarpal ligaments, and scapho-trapezio-trapezoid ligaments of a cadaveric upper extremity (n = 5). The wrist was radiographed in both anteroposterior and lateral planes to confirm creation of SLI and DISI. The scaphoid was then osteotomized at its waist. A series of grafts (1–8 mm) were then placed at the osteotomy site. Radiographs were completed at each length. The main outcome measures were scapholunate interval (SL, mm), scapholunate angle (SLA, degrees), and radiolunate angle (RLA, degrees). These values, measured following the insertion of varying graft lengths, were compared with baseline measurements taken “post-injury” status.Results The ability to create an SLI with DISI was confirmed in the postinjury group with a statistically significant change in RLA, SLA, and SL compared with preinjury. With osteotomy and progressive insertion of spacers, the values improved into the accepted normal ranges for RLA (6 mm) and SLA (4 mm) with scaphoid lengthening.Conclusions In this cadaveric model of SL injury, radiographic markers of DISI were returned to within normal ranges with scaphoid osteotomy and lengthening.Clinical Relevance The results of this study add insight into wrist kinematics in our injury model and may represent a potential future direction for surgical treatment of SLI.
Keywords: scapholunate; scaphoid; DISI